An Experimental Study on the Evaluation of Metaphorical Ad Hominem Arguments - Ervas, Francesca; Mosca, Oriana (Informal Logic, 2024)
Metaphors are emotionally engaging, influencing the evaluation of arguments. The paper empirically investigates whether metaphors in the premise can lead the evaluator to judge an ad hominem argument as sound when the arguer instead committed a fallacy. The results show that ad hominem arguments with conventional and positive metaphors are more persuasive compared to those with novel and negative metaphors. Arguments with conventional metaphors are also perceived as more ambiguous, but less convincing, and emotionally appealing. Additionally, participants believe in the conclusion more when the premise contains a positive rather than a negative metaphor, which instead helps the evaluator detect the fallacy.